Teacher Competency, Work Motivation, and Teacher Performance in BOS Kinerja Recipient Elementary Schools: A Systematic Literature Review - Rizqa Alfina Sahalia; Nuphanudin; Ainur Rifqi (Global Action and Education for Society, 2026)
This study systematically examines the relationship between teacher competency and work motivation and teacher performance in elementary schools receiving the BOS Kinerja (Performance School Grant) program. In this review, BOS Kinerja is positioned as a policy context that provides resource support for developing teacher competency and work motivation. Using a Systematic Literature Review (SLR) based on the PRISMA 2020 protocol, this review analyzes 32 scientific articles published between 2018 and 2025 from five databases: Google Scholar, Sinta, Garuda, Scopus, and ERIC. The review findings indicate that teacher competency particularly pedagogical and professional competency and work motivation are consistently reported to have positive relationships with teacher performance. In the context of BOS Kinerja recipient schools, financial support has the potential to strengthen professional development and work motivation through the provision of resources, training, and supporting facilities. However, empirical evidence specifically testing BOS Kinerja as a moderating variable remains limited; therefore, interpretations in this review are contextual rather than causal.